Telaah Kritis Terhadap Kitab-Kitab Tafsir Bi Al-Ma’tsur: Periode Ulama’ Mutaqaddimin - Aprilita Hajar (STAI Darul Kamal NW Kembang Kerang, 2022)
Tafsir Bi Al-Ma'tsur is the tafsir of the Qur'an based on the history which includes verse by verse, interpretation of verses with the sunnah of the Messenger and also interpretation with the history of the companions and tabiin. The number of contradictions and problems in interpreting the Tafsir bi Al-Ma'tsur, this should be emphasized because that the Tafsir bi Al-Ma'tsur derived from the Qur'an and the sunnah are considered valid marfu’ and must be accepted. While those from the history of sahabat or tabiin are still disputed, whether accepted or not. Although it has many advantages in terms of the source of interpretation, but it is inevitable and there must be weaknesses that have Tafsir Bil-Ma'tsur. The research method used in this discussion is literature. The urgency or results of this research can reveal the books that are sourced from Bil-Ma'tsur Tafsir, especially in the period of scholars ' Mutaqaddimin which has the characteristics of each, both in terms of methods, values, patterns, systematics of writing, opinions of scholars’ and so forth.